Workshop Aplikasi Geogebra dan Liveworksheets Bagi Guru Madrasah Tsanawiyah Negeri Se-Kota Jambi - Marni Zulyanty; Ainun Mardia; Siti Ubaidah; Rima Meslita; Defina Dwi Bulan (Jurnal Surya Masyarakat, 2024)
The development of science and technology can change the learning process, one of which is related to learning media. Existing learning media can be modified and developed according to science and technology developments. The development of science and technology in learning media, for example the GeoGebra application and live worksheets which can be used in learning mathematics. However, the use of this application is still minimal among teachers. Community service activities are a mandate for educators in tertiary institutions as a manifestation of higher education tridharma. This service is a collaboration of the Tadris Mathematics Study Program which consists of a team of lecturers, students, and the management of the Mathematics Tadris Study Program. The community service activities that have been carried out are geogebra application workshops and liveworksheets for math teachers at State MTs in the city of Jambi. As for the partners or participants in this service, representatives of two mathematics teachers from each state madrasah tsanawiyah in Jambi City. In its implementation, it can be concluded that this service activity was well organized and accompanied by extraordinary enthusiasm from the service participants.